2017
DOI: 10.11591/ijeecs.v8.i2.pp375-381
|View full text |Cite
|
Sign up to set email alerts
|

Solar Thermal Heating Acceptance Among Malaysian Industries Using System Dynamics

Abstract: <p>A solar thermal heating technology has a great potential in industries application. This paper presents a prediction of Malaysian industries acceptance on the solar thermal heating system for replacing the current heating technologies. In Malaysia, most of the heating technologies are using fossil fuel as a heating source due to the low price of the source. The solar thermal is another type of sustainable renewable energy. The objective of this research is to produce a Malaysian industries acceptance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…Another study conducted in India indicated that advertising strategies, social influence, buyer awareness, and government enterprises significantly impact purchase intentions, while environmental concern, accessibility, and cost show insignificant influences [106]. Another study conducted in Malaysia on solar thermal heaters indicated that there is a need for tailored policies to enhance the willingness to adopt even with current government support [107]. Additionally, in 2018, it was found that regulatory and structural barriers hindered market adoption of distributed energy systems [108].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in India indicated that advertising strategies, social influence, buyer awareness, and government enterprises significantly impact purchase intentions, while environmental concern, accessibility, and cost show insignificant influences [106]. Another study conducted in Malaysia on solar thermal heaters indicated that there is a need for tailored policies to enhance the willingness to adopt even with current government support [107]. Additionally, in 2018, it was found that regulatory and structural barriers hindered market adoption of distributed energy systems [108].…”
Section: Discussionmentioning
confidence: 99%